Pengembangan Pariwisata Berbasis Desa Adat di Desa Penglipuran Kabupaten Bangli - Pradnyaparamita, A.A Sri Agung (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p38, 2018)
Traditional village-based tourism development in the village of Bangli Regency Penglipuran a tourism development conducted by the Village Penglipuran. The problems of this study include (1) the form of traditional village-based tourism development and (2) the impact of tourism development based Indigenous Village. The research objective is (1) determine the form of the traditional village-based tourism development and (2) reveal how far the impact of developing a traditional village-based tourism. The method used in this research is descriptive qualitative method. Data collection techniques including observation, interview, literature study and documentation. Data analysis was performed through three simultaneous flow of activities, namely data reduction, data presentation, and conclusion. The theory used is the theory of community-based tourism and tourism impact theory. Results of this study are as follows. Traditional village-based tourism development in the village Penglipuran include tourist attraction in the village Penglipuran, the shape of the traditional village-based tourism development, and the role of indigenous villages in Penglipuran village tourism development. The impact of the traditional village-based tourism development in the village Penglipuran includes the impact of tourism on the physical environment and the natural, social, cultural, and economic. Conclusions This study is the first, the form of the traditional village-based tourism development in the village Penglipuran managing entity called Rural Tourism Organization business Penglipuran. This institution gives a role to the traditional village as the board of supervisors and the traditional village also has the authority to decide all matters related to the development of tourism. Second, the impact of the traditional village-based tourism development in the village Penglipuran the form of positive and negative impacts on the physical environment and the natural, social, cultural, and economic.